High‐charge‐capacity sputtered iridium oxide neural stimulation electrodes deposited using water vapor as a reactive plasma constituent. Issue 3 (28th July 2019) - Maeng, Jimin; Chakraborty, Bitan; Geramifard, Negar; Kang, Tong; Rihani, Rashed T.; Joshi‐Imre, Alexandra; Cogan, Stuart F.
Abstract: The deposition and properties of sputtered iridium oxide films (SIROFs) using water vapor as a reactive gas constituent are investigated for their potential as high‐charge‐capacity neural stimulation electrodes. Systematic investigation through a series of optical and electrochemical measurements reveals that the incorporation of water vapor as a reactive gas constituent, along with oxygen, alters the reduction–oxidation (redox) state of the plasma as well as its morphology and the electrochemical characteristics, including the cathodal charge‐storage capacity (CSCc ) and charge‐injection capacity (CIC), of the SIROF. An apparent optimal O2 :H2 O gas ratio of 1:3 produced SIROF with a CSCc of 182.0 mC cm −2 μm −1 (median, Q1 = 172.5, Q3 = 193.4, n = 15) and a CIC of 3.57 mC cm −2 (median, Q1 = 2.97, Q3 = 4.58, n = 12) for 300‐nm‐thick films. These values are higher than those obtained with SIROFs deposited using no water vapor by a factor of 2.3 and 1.7 for the CSCc and CIC, respectively. Additionally, the SIROF showed minimal changes in electrochemical characteristics over 10 9 pulses of constant current stimulation and showed no indication of cytotoxicity toward primary cortical neurons in a cell viability assay. These results warrant investigation of the chronic recording and stimulation capabilities of the SIROF for implantable microelectrode arrays.